"Splashy, gypsy, fertile Moju" ("Dance, Romany, my life"), a gypsy motifs in Russian poetry (on the material works of Alexander Alexandrovich Blok) = "Splaszy, cyganka, żyzń moju" ("Wytańcz, Cyganko, moje życie"), czyli o motywach cygańskich w poezji rosyjskiej (na materiale twórczości Aleksandra Aleksandrowicza Błoka) - Sobieska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a presentation and analysis of the basic symbols and meanings associated with images of Gypsy, which introduced to his works Aleksandr Blok, the most outstanding Russian poet of the beginning of the twentieth century.
Keywords: Gypsies; russian poetry; Błok, Aleksander Aleksandrowicz (1880-1921); Cyganie; Poezja rosyjska